Efektivitas Pemberian Reward Terhadap Peningkatan Kinerja Karyawan PT. Delima Makmur Aceh Singkil - Hafitz Atsram; Damrus Damrus; Afni Abdul Manan (Universitas Teuku Umar, 2023)
This literature discusses about the relation between leadership and accountability in local government. This study discusses how the effectiveness and influence of rewarding on improving the performance of employees of PT Delima Makmur Aceh Singkil and the form of rewarding in improving employee performance at PT Delima Makmur Aceh Singkil. The research in this article aims to describe how effective the improvement in employee performance that occurs with the reward program given to each employee who reaches the target or achieves. The type of research that the author uses is field research, in order to find data that is the subject matter under study. The author uses data collection techniques through direct interviews, online interviews, documentation and data from PT Delima Makmur. The data that has been obtained is processed with a qualitative descriptive method, followed by describing and dividing certain subject matter and describing through clear and easy-to-understand sentences. The results of research conducted by researchers in the field illustrate that the effectiveness of rewarding in improving employee performance at PT. Delima Makmur Aceh Singkil is in accordance with the target the company wants, rewards can also provide good motivation to each employee, all of that can be seen from the gradual achievement of the production of PT. Delima Makmur which continues to increase from year to year.